PERLINDUNGAN KONSUMEN PENGGUNA JALAN TOL JAKARTA-CIKAMPEK TERKAIT BANJIR PADA TAHUN 2021 - Chika Pratiwi; Siti Nurbaiti (Fakultas Hukum Universitas Trisakti, 2021)
Toll roads are public roads that are free of obstacles, but can also cause problems in the event of a flood, such as that occurred on the Jakarta-Cikampek Toll Road Jatibening in February 2021. What is the legal protection for consumers using the Jakarta-Cikampek toll road relating to the flooding and what are the responsibilities of the Jakarta-Cikampek Toll Road Manager on the toll road section? The research method used is a normative research method that is descriptive in nature using secondary data and primary data as supporting data. The research analysis was carried out qualitatively with deductive conclusions drawn. The results of the study illustrate that it does not provide legal protection for consumers using the Jakarta-Cikampek toll road for the Jatibening toll road during the floods that occur in 2021, because the consumer's rights in the form of the convenience of passing the toll road are not fulfilled and the Jakarta-Cikampek toll road manager for the Jatibening toll road does not provide compensation loss to toll road users against flooding, by taking cover behind force majeure reasons, even though preventing flooding on toll roads is the responsibility of toll road managers in implementing Minimum Service Standards.